Circumflex Retroesophageal Aorta Mimicking Aortic Interruption: A Rare Cause of Aortic Obstruction in a Neonate. (October 2014) - Bader, Vivian; Walayat, Mohammed; Smith, Benjamin; Davidson, Mark; Morue, Sanjay; Danton, Mark H. D.
Critical obstruction of the aorta presenting in the neonate typically occurs with aortic interruption or coarctation, following ductus arteriosus closure. Circumflex retroesophageal aortic arch is a rare aortic arch anomaly in which a right aortic arch continues as a retroesophageal component and descends on the left of the spine. Obstruction within the arch can occur, usually identified incidentally in older children. We report a neonate with circumflex aorta with ventricular septal defect in which there was hypoplasia of the retroesophageal segment. The patient presented with cardiovascular collapse following duct closure mimicking aortic interruption. The case is presented, together with the surgical repair.